The Role of Vitamin D Deficiency in the Incidence, Progression, and Complications of Type 1 Diabetes Mellitus - Marlene Chakhtoura; Sami T. Azar (International Journal of Endocrinology)
The “nonclassic” role of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) has been recently widely recognized. In type 1 diabetes mellitus (T1D), it plays an immunomodulatory role through the vitamin D receptor (VDR) present on pancreatic and immune cells. Specific VDR allelic variants have been associated with T1D in many countries. Furthermore, vitamin D deficiency has been prevalent in T1D, and the seasonal and latitude variability in the incidence of T1D can be partly explained by the related variability in vitamin D level. In fact, retrospective studies of vitamin D supplementation during pregnancy or infancy showed a lower incidence of T1D. We will review the different mechanisms of the vitamin D protective effect against insulitis and present the available data on the role of vitamin D deficiency in the control, progression, and complications of T1D.